Photoelastic Stress Analysis of Different Attachment Systems on Implant-Retained and Conventional Palatal Obturator Prostheses - Ribeiro, Paula do Prado [UNESP]; Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Haddad, Marcela Filie [UNESP]; Rosifini Alves-Rezende, Maria Cristina [UNESP]; Santos, Daniela Micheline dos [UNESP] (Lippincott Williams & Wilkins, 2011)
Background: Considering that an increasing number of patients are victims of mutilator surgical resections, these studies are important for treatment success of rehabilitation of patients presenting oronasal communication.Purpose: The aim of this study was to assess the stress distribution through photoelasticity in palatal obturator prostheses with different attachment systems for implants.Methods: Two photoelastic models were obtained from an experimental maxillary model presenting an oronasal communication. One model was fabricated without implant, and the other with 2 implants 10 mm in length inserted in the left crest. Four colorless palatal obturator prostheses were fabricated. One prosthesis presented no attachment system, whereas the remaining prostheses were adapted to 3 attachment systems. The assembly was positioned in a circular polariscope for application of axial load.Results: The results were based on photographic records of stress in the photoelastic model submitted to loading. The records revealed higher stress concentration on the bar-clip system followed by the O'ring/bar-clip and O'ring systems, respectively. A homogeneous stress distribution was observed on the photoelastic model with the mucous-supported prosthesis.Conclusions: The attachment systems generated different characteristics of stress distribution that was concentrated surrounding the implants. The bar-clip system exhibited the highest stress concentration on the alveolar crest.
Keywords: Photoelastic; implants; obturator prostheses